Ordovician magmatism in the Antigonish Highlands, Nova Scotia, Canada: A tectonic model - Murphy, J. Brendan; Archibald, Donnelly B.; Nance, R. Damian; Waldron, John W.F. (Atlantic Geoscience, 2025)
The Antigonish Highlands form part of Avalonia in mainland Nova Scotia and are predominantly underlain by ca. 620–600 Ma low grade Neoproterozoic arc-related volcanic and sedimentary rocks and coeval plutons. The highlands also preserve a record of magmatism that spans much of the Ordovician (ca. 495–455 Ma), during which time Avalonia drifted from the northern Gondwanan margin and migrated as a microcontinent ca. 2000 km northward before becoming involved in collisions with Baltica and Laurentia in the Silurian to Devonian. The longevity of Ordovician magmatism (ca. 50 Ma) is consistent with a subduction-related environment, a setting that is compatible with most paleogeographic reconstructions. However, the continental tholeiitic-alkalic within-plate affinity of the mafic rocks and the A-type signature of the felsic rocks is more typical of a back-arc setting, rather than that of a typical arc. Furthermore, the A-type felsic rocks were derived from a hotter, drier lower crust than is typical for felsic arc magmas.Whole-rock Sm-Nd isotopic data for both mafic and felsic compositions lie within previously delineated tightly constrained envelopes that define, respectively, the evolution of the Avalonian and sub-continental lithospheric mantle (SCLM), and crustal sources. These data imply that (i) the crust remained coupled to SCLM from the rifting of Avalonia from Gondwana to its accretion to Baltica in the Silurian and to Laurentia in the Early Devonian, and (ii) the Antigonish Highlands were located far from the subduction zone(s) that closed the Iapetus Ocean as it migrated northward, and so were only mildly affected by the resulting collisions.